eCM 2016
DOI: 10.22203/ecm.v031a27
|View full text |Cite
|
Sign up to set email alerts
|

Reoxygenation enhances tumour necrosis factor alpha-induced degradation of the extracellular matrix produced by chondrogenic cells

Abstract: Mesenchymal stem cells (MSCs) have been considered as a potential source for cell-based therapies in arthritic diseases for both their chondrogenic and anti-inflammatory properties. Thus, we examined how MSC-based neocartilage responds to tumour necrosis factor alpha (TNF-α) compared to articular chondrocyte (AC)-based neocartilage. Since oxygen tension is altered in arthritic joints, we also examined how increased oxygen tension influences this process. Monolayer-expanded healthy human ACs and bone marrow MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…As previously reported, TNFα exposure during the chondrogenic differentiation phase reduces chondrogenesis of MSCs (Markway et al, 2016). Although the TNFα concentrations used during chondrogenic differentiation in this in vitro study are higher than the TNFα concentrations in post-traumatic and OA joints (4-24 pg/ml, Sward et al, 2012;Tsuchida et al, 2014;Imamura et al, 2015;Alonso et al, 2020), our data indicate that in vitro pre-treatment with 50 ng/ml TNFα can be beneficial for cartilage regeneration in an inflamed environment.…”
Section: Discussionsupporting
confidence: 69%
“…As previously reported, TNFα exposure during the chondrogenic differentiation phase reduces chondrogenesis of MSCs (Markway et al, 2016). Although the TNFα concentrations used during chondrogenic differentiation in this in vitro study are higher than the TNFα concentrations in post-traumatic and OA joints (4-24 pg/ml, Sward et al, 2012;Tsuchida et al, 2014;Imamura et al, 2015;Alonso et al, 2020), our data indicate that in vitro pre-treatment with 50 ng/ml TNFα can be beneficial for cartilage regeneration in an inflamed environment.…”
Section: Discussionsupporting
confidence: 69%
“…Inflammation leads to cartilage degradation; therefore, inhibiting chondrocyte inflammation may be an efficient method for the treatment of OA. Previous studies have reported that TNF-α is a potent proinflammatory cytokine that induces apoptosis of chondrocytes, which had been enzymatically dissociated from OA knee cartilage ( 31 , 32 ). In order to study the effects of EAS treatment on TNF-α-mediated chondrocyte inflammation, a chondrocyte culture was established in vitro via stepwise 0.2% collagenase type II digestion; subsequently, the chondrocytes were treated with 10 µg/l TNF-α for various durations.…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed in the present study are due to the type of model system used, e.g. cell type, 2D vs 3D model, primary vs passage cells, free-swelling culture vs mechanical loading, uninterrupted oxygen tension using the biospherix system vs oxygen controlled incubators [47, 48]. Conversely in porcine cartilage explants, mechanical loading enhanced NO production at 5 and 20 % oxygen tension and the response was reduced at 1 % oxygen tension [11, 44].…”
Section: Discussionmentioning
confidence: 99%